Pitch control optimisation of tiltrotor aircraft - Appleton, W.; Smith, D.A.; Filippone, A.; Bojdo, N. (My University, 2021)
An investigation into the effects of rotary-wing and fixed-wing control gearings for tiltrotor aircraft was undertaken. The work investigated the effects of different cyclic and elevator gearings (both prescribed and optimised) on the longitudinal trim behaviour through the conversion regime of flight. The numerical simulations were performed for the XV-15 tiltrotor aircraft using an in-house aeromechanics code. This was coupled to a genetic algorithm to perform the optimisation studies. The findings show the control gearings must be selected carefully to maximise the conversion space and that the gearings can be optimised to meet different objective function requirements of the trim parameters. Fixed-wing control was found to be complimentary at lower airspeeds to help reduce excessive stick and cyclic inputs.